The profile of patients with oral squamous cell carcinoma under treatment in Mário Penna Hospital in Belo Horizonte, Brazil - Abdo, Evandro Neves (2002)
With the objective of assessing the epidemiological profile of patients with oral squamous cell carcinoma, interviews were conducted with 154 patients under treatment at Mário Penna Hospital in Belo Horizonte, Brazil. Patients with labial carcinoma were excluded. Most patients were male (80.5%), the mean age was 57.7 for men, and 65.7 for women. The male to female ratio for oral cancer was 4.1:1. The mean age to beginning of the addiction to smoking was 14.6 years, and to drinking, 17.6 years of age. The majority came from urban areas (80.5%), 55.2% were white, 44.8% were illiterate, and 58,9% lived on a minimum wage. Seventy nine point to three percent (79.3%) were active smokers and 48.1% were alcohol users. The mouth floor was the most site localization of the carcinoma (27.9%), followed by the tongue (22.1%) and the retromolar region (15.6%).